Nurses as Leaders in Disaster Preparedness and Response-A Call to Action - Veenema, Tener Goodwin; Griffin, Anne; Gable, Alicia R.; MacIntyre, Linda; Simons, RADM Nadine; Couig, Mary Pat; Walsh Jr, John J.; Lavin, Roberta Proffitt; Dobalian, Aram; Larson, Elaine (Journal of nursing scholarship, 2016)
Purpose To develop a vision for the future of disaster nursing, identify barriers and facilitators to achieving the vision, and develop recommendations for nursing practice, education, policy, and research. Design and Methods A series of semistructured conference calls were conducted with 14 national subject matter experts to generate relevant concepts regarding national nursing workforce preparedness. An invitational daylong workshop hosted by the Veterans Emergency Management Evaluation Center, U.S. Department of Veterans Affairs, was held in December 2014 to expand and refine these concepts. Workshop participants included 70 nurses, emergency managers, and a broad range of public health professionals. Conference call notes and audiotapes of the workshop were transcribed and thematic analysis conducted to outline a vision for the future of nursing in disaster preparedness and response, and to articulate an agenda for nursing practice, education, policy, and research to achieve that vision. Findings The group developed a vision for the future of disaster nursing, and identified current barriers and opportunities to advance professional disaster nursing. A broad array of recommendations for nursing practice, education, policy, and research, as well as implementation challenges, are summarized in this article. Conclusions This project represents an important step toward enhancing nurses’ roles as leaders, educators, responders, policymakers, and researchers in disaster preparedness and response. Nurses and the health and human service organizations that employ them are encouraged to engage in an expansive national dialogue regarding how to best incorporate the vision and recommendations into their individual lives and the organizations for which they work. Clinical Relevance Nurses comprise the largest healthcare workforce, and opportunities exist to strengthen disaster readiness, enhance national surge capacity, and build community resiliency to disasters.